EXPORT-MARKETING PROBLEMS OF SMES: THE CASE OF LUDHIANA APPARELS AND TEXTILE INDUSTRY - Vohra, Karan (2008)
Although, the benefits derived from exporting in an increasingly globalizes marketplace are enormous, but for many small-sized manufacturing firms, the internationalization path is beset by numerous challenges. This research seeks to investigate the perceived level of importance of export-marketing problems and its importance depending on the exporting experience of the firm. In light of certain gaps involving the dearth of major research in the context of Indian Apparel and Textile Industry, attempt was made examine the existence of potential differences in the perception of export marketing problems between the groups of two distinct exporter categories in terms of export market experience.